2021
DOI: 10.1155/2021/5262000
|View full text |Cite
|
Sign up to set email alerts
|

Cystic Fibrosis: Systems Biology Analysis from Homozygous p.Phe508del Variant Patients’ Samples Reveals Perturbations in Tissue-Specific Pathways

Abstract: Cystic fibrosis (CF) is an autosomal recessive disorder, caused by diverse genetic variants for the CF transmembrane conductance regulator (CFTR) protein. Among these, p.Phe508del is the most prevalent variant. The effects of this variant on the physiology of each tissue remains unknown. This study is aimed at predicting cell signaling pathways present in different tissues of fibrocystic patients, homozygous for p.Phe508del. The study involved analysis of two microarray datasets, E-GEOD-15568 and E-MTAB-360 co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 96 publications
0
2
0
Order By: Relevance
“…This work highlights that using the high-throughput screening variant of mammalian membrane two-hybrid technology can discover novel interactions of biological importance for CFTR. Poloni et al used two microarray data sets, E-GEOD-15568 and E-MTAB-360, to investigate differentially expressed genes in F508del-CFTR patients, albeit only for rectal and bronchial epithelium, respectively . The authors found that F508del-CFTR influenced the gene expression of each tissue differently; only “neutrophil activation” was shared between the tissues investigated.…”
Section: Understanding Cftr Biologymentioning
confidence: 99%
See 1 more Smart Citation
“…This work highlights that using the high-throughput screening variant of mammalian membrane two-hybrid technology can discover novel interactions of biological importance for CFTR. Poloni et al used two microarray data sets, E-GEOD-15568 and E-MTAB-360, to investigate differentially expressed genes in F508del-CFTR patients, albeit only for rectal and bronchial epithelium, respectively . The authors found that F508del-CFTR influenced the gene expression of each tissue differently; only “neutrophil activation” was shared between the tissues investigated.…”
Section: Understanding Cftr Biologymentioning
confidence: 99%
“…Poloni et al used two microarray data sets, E-GEOD-15568 and E-MTAB-360, to investigate differentially expressed genes in F508del-CFTR patients, albeit only for rectal and bronchial epithelium, respectively. 41 The authors found that F508del-CFTR influenced the gene expression of each tissue differently; only "neutrophil activation" was shared between the tissues investigated. This suggests a comprehensive insight into the molecular networks of CF epithelia (albeit limited to bronchial and rectal epithelia) and the underlying regulators involved in CF.…”
Section: Fetuses and Newborns With Cystic Fibrosismentioning
confidence: 99%